Control Systems Engineering. - Bhattacharya, Sanjib Kumar (2011)
Control Systems Engineering is a comprehensive text designed to cover the complete syllabi of the subject offered at various engineering disciplines at the undergraduate level. The book begins with a discussion on open-loop and closed-loop control systems. The block diagram representation and reduction techniques have been used to arrive at the transfer function of systems. The signal flow graph technique has also been explained with the same objective. This book lays emphasis on the practical applications along with the explanation of key concepts.
Concept of State-Variable Modelling -- Control Components -- Key Terms -- Bibliography -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books